Legal Analysis of the Classification of Marijuana as a Class I Narcotic Under the Narcotics Law - Yulizar Yulizar; Mohd. Din; Adwani Adwani (International Journal of Sociology and Law, 2026)
The circulation of narcotics as a serious crime in Indonesia faces the reality that some types of narcotics have medical benefits when used in limited quantities and under strict supervision, while cannabis plants remain classified as Class I Narcotics in Law No. 35 of 2009 concerning Narcotics, thereby prohibiting their use in health services. This situation raises legal issues regarding the basis for classification, legal qualifications, and the possibility of updating norms so that cannabis can be used for medical purposes. This study aims to analyze the historical and legal basis for the classification of cannabis, its qualification in the national legal system, and to formulate a normative regulatory concept that allows its use for health services. The method used is normative legal research with a historical and comparative approach, through a literature study of primary and secondary legal materials, which are analyzed descriptively and qualitatively. The results of the study show that the classification of cannabis is rooted in international commitments through the 1961 Single Convention on Narcotic Drugs, which was later ratified and adopted into national law, so that legally cannabis is only permitted for research purposes. however, considering the development of science and practice in various countries, it is necessary to update the norms through the formation of a Ministerial Regulation as mandated by Article 6 paragraph (3) of the Narcotics Law as a limited and controlled first step to open up the use of cannabis in health services without neglecting the principle of preventing abuse.